LEMBAGA PENDIDIKAN: REFLEKSI DAYAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM DI ACEH - jufrizal jufrizal (Institute of Information Technology and Social Science (IITSS), 2021)
A typical educational institution in Aceh called Dayah is an institution that initially positioned itself as an educational center for cadre of scholars. Its presence as an Islamic educational institution in Aceh can be estimated almost simultaneously with the presence of Islam in the archipelago. Dayah has four very significant uses for the people of Aceh, namely as a center of religious learning, as a bulwark against forces against colonial penetration, as an agent of development, and as a school for the community. In its development, the religion of Islam continues to progress and is deeply rooted in society through the roles and struggles of the ulama. This is done together with the educational institution he built, nurtured and fostered, namely Dayah. This educational institution in addition to acting as a place for learning and educating cadres of ulama and Acehnese leaders on an ongoing basis also plays a major role as a social institution that provides many services and initiatives for the empowerment of the surrounding community. It is proven that not only in the past, but until now, dayah alumni not only act as educators but also as role models for the community.